THE UNFULFILLED LOVE NEED IN THE MAIN CHARACTER OF ANTON CHEKOV’S MISERY - MARIA, GRACE IVONE (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Needs fulfillment, basic needs, love needsHuman beings have to fulfill their needs to support their daily life. In this case, between needs and wants has to be balanced in order to avoid imbalance which can raise the problem. Considering about the importance of fulfilling the basic needs, the writer observes about needs fulfillment that is in the short story Misery. This short story is narrated about the sadness of someone who loses his son until he neglects his needs. Hence, in this study, the writer will answer the problem of the study that is (1) what kind of problems appear from the unfulfilled love need in the main character of Anton Chekov’s Misery? (2) How can these problems happen to the main character of Anton Chekov’s Misery?The study is using a qualitative approach to describe the event that is clearlyand systematically learnt. The contextual description study is used with the purpose to analyze the short story Misery.The result of the study shows that basic needs (physiological needs, safetyneeds, love and belonging needs, and esteem needs) which cannot be fulfilled will make complex problems. In order to solve his problems, he tries to talk to his passenger, but he is neglected. There is an imbalance between Iona’s need and desire so he misses many things. Iona’s unconsciousness when he neglects his basic needs becomes the principal point of view of the writer.